Incidence and Clinical Significance of Worsening Tricuspid Regurgitation Following Surgical or Transcatheter Aortic Valve Replacement: Analysis From the PARTNER IIA Trial. (16th July 2021) - Cremer, Paul C.; Wang, Tom Kai Ming; Rodriguez, L. Leonardo; Lindman, Brian R.; Zhang, Yiran; Zajarias, Alan; Hahn, Rebecca T.; Lerakis, Stamatios; Malaisrie, S. Chris; Douglas, Pamela S.; Pibarot, Philippe; Svensson, Lars G.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Aortic valve replacement (AVR) is recommended for severe symptomatic aortic stenosis. However, the incidence of worsening tricuspid regurgitation (TR) following transcatheter compared with surgical AVR (TAVR, SAVR), and the impact of worsening TR on outcomes, is ill-defined. Accordingly, among patients randomized to TAVR or SAVR, we describe the differential incidence of worsening TR and its association with survival. Methods: From the PARTNER IIA trial (Placement of Aortic Transcatheter Valves IIA), 1334 patients were included with baseline and 30-day postprocedure core-lab echocardiograms. Worsening TR was defined as deterioration of ≥1 grade from baseline to 30 days. Outcomes included cardiovascular and all-cause death between 30 days and 2 years. Multivariable logistic regression was performed to identify associations with worsening TR; survival analyses were performed to assess associations with mortality. Results: Worsening TR occurred in 17.3% (125/721) of TAVR and 27.0% (165/611) of SAVR patients. On multivariable analysis, SAVR (odds ratio, 2.09 [95% CI, 1.40–3.11]), female sex (odds ratio, 2.22 [95% CI, 1.44–3.42]), atrial fibrillation (odds ratio, 1.61 [95% CI, 1.03–2.51]), and right ventricular enlargement (odds ratio, 2.25 [95% CI, 1.17–4.31]) were associated with worsening TR. Cardiovascular and all-cause death occurred in 9.0% (26/290) and 17.9% (52/290) of patients with worsening TR, compared with 4.8% (50/1042) and 10.9% (114/1042) without worsening TR, respectively. In patients with worsening TR, cardiovascular and all-cause death were similar in TAVR compared with SAVR, (hazard ratio, 1.09 [95% CI, 0.55–2.16]) and (hazard ratio, 1.07 [95% CI, 0.62–1.87]), respectively. After adjustment, worsening TR was independently associated with cardiovascular (hazard ratio, 3.62 [95% CI, 2.08–6.29]) and all-cause death (hazard ratio, 2.11 [95% CI, 1.37–3.27]). Conclusions: Worsening TR is associated with female sex, atrial fibrillation, right ventricular enlargement, and SAVR. Regardless of mode of AVR, worsening TR is similarly associated with a poor prognosis. Future studies should focus on whether preventing or treating worsening TR improves outcomes. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01314313.